A Conceptual Framework of Cost and Benefit Analysis on Airport Road Access Wayfinding - Nur Khairiel Anuar; Rohafiz Sabar (International Journal of Supply Chain Management, 2018)
The inclusion of cost and benefit analysis (CBA) on the airport road access wayfinding design is important. Standard CBA was used to determine the additional costs incurred and benefits from airport road access wayfinding development. This concept paper explains the willingness to trade-off between the social benefits and the cost comparison of airport road access wayfinding design. The importance of airport cost and benefit structures and their influence on the decision-making process for the provision of airport road access wayfinding was considered. The key issues were then analysed and presented; costs (i.e. investment, operating, maintenance, and fuel consumption costs); benefits (i.e. travel time, accident reduction savings, and airport road advertising revenue). The CBA is an appropriate technique for the airport road access wayfinding appraisal. It has an explicit normative basis and was performed for the purpose of guidelines of informing airport management and road sign design professionals that the alternative airport road access wayfinding with the largest positive Net Present Value (NPV) and Benefit-Cost Ratio (BCR) exceeding 1.0 would be given primary consideration as the preferred course of action.